Penegakan Hukum Terhadap Penyedia Fasilitas Yang Memberikan Peluang Terjadinya Jarimah Maisir - Airi Safrijal; Sahardiani Sahardiani (Jurnal Hukum dan Keadilan "MEDIASI", 2018)
Enforcement of jinayat law against organizers and providers of facilities / places that can occur Maisir (gambling) in the city of Banda Aceh is currently not in accordance with applicable regulations as stated in Article 20 of Qanun Number 6 of 2014 on Jinayat Law, namely "Every person who intentionally organizes, provides facilities, or finances to Jarimah Maisir (gambling) as referred in Article 18 and Article 19 of the Qanun is threatened with 'Uqubat Ta'zir (caning) at most 45 (forty five) times and/or a maximum fine of 450 (four hundred fifty) grams of pure gold and/or imprisonment of no longer than 45 (forty five) months”. Thereare several things that need to be considered by Banda Aceh City governmentrelated to the implementation of the Jinayat Law in Aceh, namely optimizing theapplication of caning, as well as increasing community participation in theenforcement of Islamic Sharia.